World economic growth: trends, country factors, social progress (Farabi Journal of Social Sciences, 2019)
Abstract. The state and prospects of world economy are analyzed. Country factors, effecting on the GDPfigures and changes of GDP in the trend were revealed. World economic problems, expressed in dynamic`sdecline, started to appear in the pre-crisis period. Despite the lower rates of economic growth than previouslyin the developed countries, world economy has positive dynamics due to large fast-growing economy. In thisconnection, it was important to do the analysis and forecast of the impact of individual countries on worldeconomic growth, on the one hand, and the impact of fast-growing economy on social progress in their owncountries.